Differential transcriptome response of blood brain barrier spheroids to neuroinvasive Neisseria and Borrelia - Kulkarni, Amod; Jozefiaková, Jana; Bhide, Katarína; Mochnaćová, Evelína; Bhide, Mangesh (Frontiers in Cellular and Infection Microbiology, 2023)
Background The blood-brain barrier (BBB), a highly regulated interface between the blood and the brain, prevents blood-borne substances and pathogens from entering the CNS. Nevertheless, pathogens like Neisseria meningitidis and Borrelia bavariensis can breach the BBB and infect the brain parenchyma. The self-assembling BBB-spheroids can simulate the cross talk occurring between the cells of the barrier and neuroinvasive pathogens. Methods BBB spheroids were generated by co-culturing human brain microvascular endothelial cells (hBMECs), pericytes and astrocytes. The BBB attributes of spheroids were confirmed by mapping the localization of cells, observing permeability of angiopep2 and non-permeability of dextran. Fluorescent Neisseria, Borrelia or E. coli (non-neuroinvasive) were incubated with spheroids to observe the adherence, invasion and spheroid integrity. Transcriptome analysis with NGS was employed to investigate the response of BBB cells to infections. Results hBMECs were localized throughout the spheroids, whereas pericytes and astrocytes were concentrated around the core. Within 1 hr of exposure, Neisseria and Borrelia adhered to spheroids, and their microcolonization increased from 5 to 24 hrs. Integrity of spheroids was compromised by both Neisseria and Borrelia, but not by E. coli infection. Transcriptome analysis revealed a significant change in the expression of 781 genes (467 up and 314 down regulated) in spheroids infected with Neisseria, while Borrelia altered the expression of 621 genes (225 up and 396 down regulated). The differentially expressed genes could be clustered into various biological pathways like cell adhesion, extracellular matrix related, metallothionines, members of TGF beta, WNT signaling, and immune response. Among the differentially expressed genes, 455 (48%) genes were inversely expressed during Neisseria and Borrelia infection. Conclusion The self-assembling spheroids were used to perceive the BBB response to neuroinvasive pathogens - Neisseria and Borrelia. Compromised integrity of spheroids during Neisseria and Borrelia infection as opposed to its intactness and non-adherence of E. coli (non-neuroinvasive) denotes the pathogen dependent fate of BBB. Genes categorized into various biological functions indicated weakened barrier properties of BBB and heightened innate immune response. Inverse expression of 48% genes commonly identified during Neisseria and Borrelia infection exemplifies unique response of BBB to varying neuropathogens.